UJI KESESUAIAN CT NUMBER IN WATER PADA PESAWAT CT SCAN MERK PHILIP DI INSTALASI RADIOLOGI RSU. BMC PADANG : THE COMPATIBILITY TEST OF CT NUMBER IN WATER ON CT SCAN AIRCRAFT BRAND PHILIP IN RADIOLOGY INSTALLATION OF BMC PADANG GENERAL HOSPITAL - Nansih, Livia Ade; Artitin, Cicilia (JURNAL TERAS KESEHATAN, 2023)
CT number is the value of the X-ray attenuation coefficient determined by the average energy of X-rays and the absorber atomic number is expressed by the attenuation coefficient. The role of the CT number on a CT scan machine to assess and differentiate abnormalities in human organs. Compliance tests are carried out to ensure that the CT-Scan aircraft meets radiation safety requirements and provides precise and accurate diagnostic information. This research is a quantitative research with an experimental approach, carried out at the Radiology Installation of RSU Bunda Padang in June 2022 for 5 days. The population of all CT number tests, samples at five measurement points with ROI in the center of the image, at 12 o'clock, 3 o'clock, 6 o'clock and 9 o'clock directions. Research data was taken by observing, experimenting and documenting. Data analysis was compared with PERKA BAPETEN Number 9 of 2011 concerning quality assurance of QA and QC of CT Scan aircraft. The results showed that the CT number value in the middle of the image on the first day was 4.83 HU, the second was 4.83 HU, the third was 4.14 HU, the fourth was 5.15 HU and the fifth was 5.16 HU while the average standard deviation on the first day was 3, 48 HU, the second day 3.42 HU, the third day 3.41 HU, the fourth day 3.43 HU and the fifth day 3.50 HU, the ROI uniformity results at the image and noise center show that it has exceeded the tolerance limits set by PERKA BAPETEN No. 9 of 2011.